Surplus to Requirements: Work, Non-Linearity, and Abduction in Creative Research - Madero, María Angélica; Carney, James (Imaginations, 2024)
We argue that the institutional administration of academic and creative research as labor does violence to the true character of this research as work. Where work is a pluralist concept that admits multiple forms of transformation, labor is based on a linear proportionality of inputs to outputs. We explore various forms of non-linearity in creative work and pedagogical work, ranging across disproportion, the associative, the counterfactual, and the interdisciplinary. We arrive at C.S. Peirce’s notion of semiotic abduction as a useful cognitive model for research practice and creation. Here, the linear mapping of inputs to outputs is complemented by a recognition of the role played by the speculative or interpretive leap in arriving at novel concepts and practices.